A review on the irrebutabble presumption of law that a boy under the age of thirteen years is incapable of committing rape (Section 113 Evidence Act 1950) / Muhammad Sabre Jabar - Jabar, Muhammad Sabre (2014)
The issue of rape among child offender had been crucial nowadays. Despite reported rape cases in Malaysia, there are numbers of cases were unreported cases due to the idea of not to tarnish the reputation of the accused child as he might have brighter future, assumption of incapability of rational thinking and sexual intelligence by a child as well as to protect the good names of the family. There is an urgent need for the review of the presumption, to uphold justice at the right place. This research aims to review the irrebutabble presumption of law that a boy under the age of thirteen years is incapable of committing rape as stipulated in Section 113 Evidence Act 1950. Besides, the research aims to lowering the age of criminal responsibility for rape in this section, to be at uniform phase with Section 82 and 83 of Penal Code, or abolished it and solely refers to the Penal Code as a single law referred. Meanwhile, this research is based on data obtained from a survey through questionnaire that polled on the kids from urban area, sub-urban and rural schools. The data was analyzed to evaluate and determine the sexual knowledge of the kids, the attitude towards sexual issues confronted to them and legal information possessed by the children. Furthermore, interviews from some scholars will be taken place as supporting evidence to lowering the age of criminal responsibility for rape in this section, or abolished it. It is hope that this research may help the policy maker and legislators to review the importance of combatting rape cases involving child offender in Malaysia.